Left ventricular (LV) pacing in newborns and infants: Echo assessment of LV systolic function and synchrony at 5‐year follow‐up. Issue 6 (22nd April 2020) - Silvetti, Massimo Stefano; Muzi, Giulia; Unolt, Marta; D'Anna, Carolina; Saputo, Fabio Anselmo; Di Mambro, Corrado; Albanese, Sonia; Ammirati, Antonio; Ravà, Lucilla; Drago, Fabrizio
Abstract: Background: Small retrospective studies reported that left ventricular (LV) pacing is likely to preserve LV function in children with isolated congenital complete atrioventricular block (CCAVB). The aim of this study was to prospectively evaluate LV contractility and synchrony in a cohort of neonates/infants at pacemaker implantation and follow‐up. Methods: Patients with CCAVB who underwent LV pacing were evaluated with electrocardiogram and echocardiogram in a single‐center, prospective study. Data were collected at implantation, at 1‐month and every year of follow‐up, up to 5 years. LV ventricular dimensions (diameters and volumes), systolic function (ejection fraction [EF] and global longitudinal strain [GLS]), and synchrony were evaluated. Data are reported as median (25th‐75th centiles). Results: Twenty consecutive patients with CCAVB underwent pacemaker implantation (12 single‐chamber pacemaker [VVIR] and eight dual‐chamber pacemaker [DDD]) with epicardial leads: 17 on the LV apex and three on the free wall. Age at implantation was 0.3 months (1 day‐4.5 months). Patients showed good clinical status, normal LV dimensions, preserved systolic function, and synchrony at 60 (30‐60) months follow‐up. EF increased to normal values in patients with preimplantation EF <50%. Presence of antibodies and pacing mode (DDD vs VVIR) had no impact on the outcome. Conclusions: LV pacing preserved LV systolic function and synchrony in neonates and infants with CCAVB at 5‐year follow‐up. LV EF improved in patients with low preimplantation EF. Pacing mode or the presence of autoantibodies did not demonstrated an impact on LV contractility and synchrony.